Financial advice and gender: Wealthy individual investors in the UK - Baeckström, Ylva; Marsh, Ian W.; Silvester, Joanne (Journal of Corporate Finance, 2021)
We examine how gender differences in investment risk tolerance, knowledge, confidence and portfolio cash allocations relate to the gender mix of investors and financial advisors among a sample of wealthy individuals in the UK. Our results demonstrate that gender effects are more nuanced than previously assumed. First, while even wealthy women consider themselves more conservative and allocate a higher proportion of their investable assets to cash than men, previous findings of lower investment knowledge and confidence do not extend to our sample. Second, having an advisor matters. Advised investors perceive themselves to have a higher risk tolerance and invest 10.6%-points more than self-directed investors. Finally, the investor-advisor gender combination matters, but only for female investors. Women with male advisors are more risk averse, feel less knowledgeable and less confident about their investment decisions. They also invest 11%-points less than women with female advisors. Indeed, female investors advised by women report the highest risk tolerance and make the lowest portfolio allocation to risk-free assets across the full sample, including men.